EKSTRAKSI MINYAK ATSIRI BUNGA MELATI: PENGARUH RASIO MASSA BUNGA MELATI DENGAN VOLUME PELARUT N-HEKSANA, WAKTU EKSTRAKSI, DAN TEMPERATUR EKSTRAKSI - Michael Dillo Rizki Ginting; Febrina Iskandar; Iriany; Okta Bani (Talenta Publisher (Universitas Sumatera Utara), 2019)
Jasmine flower (Jasminum sambac) contains essential oil compounds. Jasmine flower essential oil is a high-quality essential oil. Essential oils are volatile oils that have aroma similar to the original plant. Jasmine flower essential oil is sought due to its calming and anti-depression nature. In this study, the effect of extraction temperature, extraction time and solvent to jasmine flower ratio on jasmine oil was studied. The extraction was carried out at 30oC, 35oC, and 40oC for 2 hours, 3 hours, 4 hours, and 5 hours by using n-hexane. The ratio of jasmine flower to n-hexanes were 1:3; 1:4; and 1:5 (w/v). Resulting jasmine oil was analyzed by GC-MS, and its quality was assessed according to SNI 06-2385-2006 which include colour test, refractive index analysis, acid number analysis, and ester number analysis. This experiment showed that increasing of extraction time, extraction temperature, and volume of solvent lead to increase of absolute yield of jasmine essential oil. The highest jasmine oil yield obtained at 11.69 %. The jasmine oil contained was 47.14 % benzyl acetate and had yellow color. Its refractive index, acid number, and ester number were 1.478, 20.92 mg KOH/gram jasmine essential oil, and 150.27 mg KOH/gram jasmine essential oil respectively.